(untitled) (Annals of Medical Research, 2021)
Aim: Alopecia areata (AA) is a clinical manifestation that is characterized with hair loss with hairs in sharp borders, and in a round or oval shape on the scalp or in any part of the body. It is considered that genetic factors, infections, autoimmune factors, neuropeptides and psychological factors play roles in its etiopathogenesis. As psychological traumas have an important role in the onset and exacerbation period of the disease, it is also considered as a psychosomatic one. Distress Tolerance (DT) is defined as the capacity to experience and survive negative psychological situations. DT is considered important in etiopathogenesis of diseases, and it is also considered as one of the factors that determine the response to treatment and is targeted to increase in psychotherapy. In the present study, the purpose was to determine the Distress Tolerance levels of AA patients, and compare them with healthy controls.Material and Methods: A total of 36 patients, who applied to the dermatology clinic, and who did not have any other diseases except AA, were included in the study. In the Control Group, 36 healthy volunteers, who were matched in terms of age and gender with the Patient Group, and who did not have any physical or mental illness, were included. The Sociodemographic and Clinical Data Form (SCDF), Distress Tolerance Scale (DTS), and Hospital Anxiety and Depression Scale (HADS) were given to the Patient and Control Group.Results: No significant differences were detected between the groups in terms of age and gender. A significant difference was detected in the Patient Group in terms of both the total score of DTS (p0.001) and the DTS tolerance, DTS regulation and DTS self-efficacy subscales (p=0.004, p=0.008, p=0.006, respectively). When the groups were analyzed in terms of HADS results, the anxiety levels were higher at a significant level in the Patient Group (p0.001), and no significant differences were detected in terms of depression scores (p=0.57).Conclusions: In this study, the DT levels were determined as low in AA patients. The DT levels in AA, which is also considered as a psychosomatic disease, might be important for the onset, course and treatment of the disease. Meanwhile, it may also be aimed to increase the DT levels during the psychotherapy process.